Implementasi Manajemen Pembelajaran dalam Mewujudkan Budaya Religius di Lembaga Pendidikan Islam - Olivia Maunti; Nasrudin Harahap; Nurul Hidayati Murtafiah (Journal on Education, 2023)
This exploration plans to decide the execution of learning the executives in understanding the strict culture of understudies in Islamic instructive organizations. This kind of exploration utilizes writing/library studies. The creator gathers different writing connected with specific points, in particular working on the nature of training and funding of schooling. Then it is gathered through classification of different writing, the two books and diaries connected with the material. The consequences of the examination show that to frame a strict understudy character, methodologies are expected to make a strict culture at school. These procedures incorporate the accompanying techniques: Working on the nature of learning should be completed methodicallly where learning components, including goals, materials, methodologies and assessment, should be coordinated and interrelated. In accordance with the point of schooling that instructive organizations should foster strict culture in Islamic instructive foundations, thusly extracurricular exercises, particularly in the field of religion, are extremely useful in creating learning in Islamic instructive establishments, particularly in creating strict culture. Imparting strict qualities in Islamic instructive establishments